A Case Report On Cutaneous Leiomyosarcoma with Review of Literatures (Journal of Current and Advance Medical Research, 2018)
Cutaneous leiomyosarcoma represents superficial form of leiomyosarcoma which is a rare mesenchymal tumour originating from smooth muscle cells. Clinically cutaneous leiomyosarcoma can be confused with other cutaneous tumour and needs histopathology and immunohistochemistry to confirm the diagnosis. As it is an uncommon malignant neoplasm we encouraged reporting this case who presented to our hospital as an irregular nodular cutaneous lump of short duration in her right thigh. After local excision histopathological examination of excised specimen established the diagnosis of cutaneous leiomyosarcoma. A brief review of literature is also included here.Journal of Current and Advance Medical Research 2017;4(2):63-67